The Role of the General Plan in the Development of Modern Cities on the Example of St. Petersburg - M. V. Minina; D. A. Rehakkainen (Управленческое консультирование)
This article discusses the process of forming the General Plan of St. Petersburg. The short-comings of the existing General Plan of St. Petersburg are revealed. The concepts of the General Plan, territorial planning documents, the process of making changes to the General Plan of St. Petersburg are analyzed. Based on the conducted research, the author proposed a solution aimed at the optimal functioning of the General Plan.